Crude oil hierarchical catalytic cracking for maximizing chemicals production: Pilot-scale test, process optimization strategy, techno-economic-society-environment assessment. (1st February 2022) - Zhou, Xin; Li, Shangfeng; Wang, Yuan; Zhang, Jiewenjing; Zhang, Zhibo; Wu, Changgui; Chen, Xiaobo; Feng, Xiang; Liu, Yibin; Zhao, Hui; Yan, Hao; Yang, Chaohe
Graphic abstract: This study first proposed the crude oil hierarchical catalytic cracking process. Detailed process simulation, optimization strategy, and life cycle assessment were executed. Results elucidated that the novel process has positive guidance and reference significance to the techno-economic-society-environment. Highlights: Crude oil hierarchical catalytic cracking for maximizing chemicals production is simulated. A systematical process integration and optimization strategy protocol is adopted. The techno-economic-society-environment performance is compared quantitatively. The crude oil hierarchical catalytic cracking process shows superior performance. Abstract: Crude oil direct catalytic cracking can effectively promote the production of chemicals. However, the heterogeneity of cracking depth of various distillates seriously restricts its industrialization. This study proposed a novel crude oil hierarchical catalytic cracking process for controlling the catalytic cracking depth. The key operating parameters were investigated and optimized using a multi-objective optimization strategy. A quantitative assessment for the life cycle techno-economic-society-environment of the novel processes was then conducted and compared with the conventional process. Results show that the optimized first and second flash unit temperatures are 187 °C and 251 °C. The optimized first and second riser outlet temperatures are 644 °C and 682 °C, respectively. The conversion rate and olefin yields of the novel process are increased by 1.47% and 1.46%. The hydrogen and carbon atoms efficiency in the novel process is 63.17% and 76.21%, which could raise 0.97% and 1.62% compared with the conventional process. Moreover, the novel process could increase 14.3% and 1.61%% in the net present value and internal rate of return. Meanwhile, it decreased by 2.1%, 8.2%, and 2.2% in greenhouse gas emissions, wastewater generation, and non-renewable energy consumption, compared with conventional crude oil-to-chemicals processes. These findings in this work could promote engineering application, process intensification, and key operating parameters optimization of crude oil direct catalytic cracking.